(untitled) (Journal of Artificial Intelligence Research, 2024)
Multi-agent systems (MAS) consist of autonomous agents that interact with each other to achieve individual and collective goals. Coordination and cooperation among agents are crucial for achieving efficient and effective outcomes in MAS. This paper provides a comprehensive overview of coordination and cooperation mechanisms in MAS, focusing on their principles, challenges, and applications. Various coordination strategies, such as task allocation, communication protocols, and negotiation mechanisms, are discussed in detail. Additionally, the paper examines the role of cooperation in MAS, highlighting how agents can collaborate to enhance performance and achieve collective goals. The challenges associated with coordination and cooperation, including scalability, robustness, and privacy concerns, are also addressed. Finally, the paper explores future research directions and potential applications of coordination and cooperation mechanisms in MAS.